Formation, microstructure and properties of aluminum borate ceramics obtained from alumina and boric acid - Hernández, María Florencia (2017)
The formation of aluminum borates (Al18B4O33 and Al4B2O9) from alumina and boron oxide occurs between 600 and 800 °C. These materials have refractory properties and corrosion resistance. The objective of this work is to develop materials from the Al2O3-B2O3 system, employing alumina and boric acid as starting powders, to study the critical processing variables and describe the developed microstructure and properties. Three formulations (13, 19.5 and 26 wt% B2O3) were studied. In order to confirm the formation of borates, the differential thermal analysis and thermogravimetric analysis were carried out. Afterwards, uniaxially pressed disc-shaped specimens were fired at four temperatures above the formation temperature. The textural properties of the ceramics were evaluated by the immersion method, this permit to evaluate the sintering processes. Then the degree of borate formation was confirmed by X-ray diffraction. Finally, the developed microstructures were characterized by scanning electron microscopy, and the diametral compression behavior was evaluated. A series of porous (≈50%) refractory materials from the Al2O3-B2O3 system were developed. The processing strategy resulted in materials with Al18B4O33 as the main crystalline phase. Needle grains with diameters between 0.2 and 1 μm and an aspect ratio over 20:1 were obtained. Thus, based on the information gathered from our research, aluminum borate ceramic materials can be designed for structural, insulating or filtering applications employing only alumina and boric acid as boron oxide source.